Effectiveness of phototherapy in reducing pathological jaundice in newborns at Tenriawaru Hospital - Marhayana; Hasnidar; Hasliana; Sulfianti (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Pathological jaundice remains a common neonatal condition characterized by an excessive rise in serum bilirubin, which may lead to severe complications such as acute bilirubin encephalopathy and kernicterus if not promptly treated. Phototherapy is the primary non-invasive intervention used to lower bilirubin levels by converting unconjugated bilirubin into water-soluble forms. Increasing cases of neonatal jaundice reported at Tenriawaru Hospital highlight the need to evaluate the clinical effectiveness of phototherapy within this setting. This study aims to determine the efficacy of phototherapy in reducing bilirubin levels among newborns diagnosed with pathological jaundice at Tenriawaru Hospital, Bone. Methods: This quantitative descriptive study used secondary data obtained from neonatal medical records. Variables assessed included gestational age, initial bilirubin levels, duration of phototherapy, and post-therapy bilirubin levels. Data were analyzed using the chi-square test at the 0.05 significance level to identify associations between clinical factors and phototherapy outcomes. Results: A total of 84 newborns with pathological jaundice underwent phototherapy. There was a statistically significant reduction in bilirubin levels after phototherapy (p = 0.000), indicating a strong therapeutic effect. The duration of phototherapy and the initial bilirubin concentration were found to influence treatment effectiveness, with more prolonged therapy associated with greater reductions in bilirubin. Conclusion: Phototherapy is highly effective in reducing serum bilirubin levels among newborns with pathological jaundice at Tenriawaru Hospital. Timely initiation and adequate duration of phototherapy are critical for preventing complications and improving neonatal outcomes.